Analisis Take-Home Pay dan Perencanaan Anggaran terhadap Sustainabilitas Program Jaminan Kesehatan Nasional - Ridwan Ridwan; Doly Siregar (Jurnal Jaminan Kesehatan Nasional, 2021)
Abstract: Dynamic regulation changes in JKN Program are made by the government to maintain the program’s financial health and sustainability by increasing the contributions, but the local government budget weakening during the Covid-19 pandemic is resulting in contribution receivable increasing. This study aims to compare the contributions from the collection of Civil Servant salaries and local government subsidies based on take-home pay compared to the previous calculation and the effect on the civil servants to analyze the compliance of local government budget planning and the obstacles on the budget insufficiency. This study uses a case study through the qualitative method with a descriptive analysis approach, this research uses secondary data in the form of documents and primary data in the form of interviews. The samples are conducted by purposive sampling as many as 127,341 civil servants in Aceh Province. The results showed the potential for an increase in income of 140.81 billion rupiahs, which was an increase of 47.52%. In total, the payment of contributions by deductions from the salaries of civil servants decreased by 281%. On the other hand, the contribution paid by the local government increased by 203%. In terms of budget, 5 of the 24 local governments have provided their budget availability for a 4% contribution. The regulation changes have positive impacts on the sustainability of the JKN program by increasing the program’s income and realizing mutual cooperation with equitable contribution and the involvement of local governments through a larger portion of the contribution budget. Coordination and guidance improvement between the central government and local government to monitor the implementation of Presidential Regulation Number 75 of 2019 as a national priority program and sanction enforcement for local governments which are in contribution arrears and insufficient budget. Keywords: take-home pay; budgeting; sustainability; JKN Program